Inter-model analysis of tsunami-induced coastal currents. (June 2017) - Lynett, Patrick J.; Gately, Kara; Wilson, Rick; Montoya, Luis; Arcas, Diego; Aytore, Betul; Bai, Yefei; Bricker, Jeremy D.; Castro, Manuel J.; Cheung, Kwok Fai; David, C. Gabriel; Dogan, Gozde Guney; et al.
Highlights: Results of a community benchmarking exercise for tsunami currents are presented. Model tests focus on tsunami-induced currents that are shear and separation driven. Areas affected by large-scale eddies have the greatest inter-model variability. The need for a statistical modeling approach for eddy-affected areas is discussed. Abstract: To help produce accurate and consistent maritime hazard products, the National Tsunami Hazard Mitigation Program organized a benchmarking workshop to evaluate the numerical modeling of tsunami currents. Thirteen teams of international researchers, using a set of tsunami models currently utilized for hazard mitigation studies, presented results for a series of benchmarking problems; these results are summarized in this paper. Comparisons focus on physical situations where the currents are shear and separation driven, and are thus de-coupled from the incident tsunami waveform. In general, we find that models of increasing physical complexity provide better accuracy, and that low-order three-dimensional models are superior to high-order two-dimensional models. Inside separation zones and in areas strongly affected by eddies, the magnitude of both model-data errors and inter-model differences can be the same as the magnitude of the mean flow. Thus, we make arguments for the need of an ensemble modeling approach for areas affected by large-scale turbulent eddies, where deterministic simulation may be misleading. As a result of the analyses presented herein, we expect that tsunami modelers now have a better awareness of their ability to accurately capture the physics of tsunami currents, and therefore a better understanding of how to use these simulation tools for hazard assessment and mitigation efforts.